Diseño de un modelo de planeación estratégica para una empresa de limpieza y transporte de materiales y residuos contaminantes. Aplicación práctica en la empresa Servitem. - Ocaña Ramos, Cristian Iván (2012)
Servitem is the name of the company where the following research work focused on the design of a strategic planning by management's analysis, with emphasis in accounting and economics develops. That is, an organization dedicated to the collection, transportation and disposal of solid waste similar to household from grease traps, food waste for composting wastewater and septic tanks.